INDONESIAN HERBS WITH ANTIFERTILITY EFFECTS ON MEN: A SYSTEMATIC REVIEW - Ainur, Syafrida; Widyawati, Melyana Nurul (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2019)
Background: The attention and implementation of family planning programs in Indonesia tends to focus on women. Meanwhile, male contraception method has fewer types than female ones. Various herbs in Indonesia have showed potential antifertility effects on men. The objectives of this study is to identify and analyze the results of studies on the effects of Indonesian herbs on male antifertility.Methods: This was a systematic review using several articles obtained from Science Direct, PubMed, Wiley Online Library, Google Scholar, and Garba Rujukan Digital databases. The inclusion criteria in this study were experimental research of the effects of herbs on antifertility; samples of studies included male mice, long-tailed male monkeys, and human sperm; and full-text article available.Results: The literature search returned 1420 articles, of which 37 studies were included in the systematic review. Different Indonesian herbs were observed, such as Carica papaya (n = 8), Momordica charantia (n = 7), Piper betle (n = 5), Hibiscus rosa (n = 5), Curcuma domestica (n = 4), Areca catechu (n = 4), and Andrographis paniculata (n = 4) have been identify with different effects. Antifertility effects observed including antispermatogenic, sperm quality reduction, and the changing of the histology of reproductive organs.Conclusions: Indonesian herbs are portentially used as new contraceptive methods for male subjects such as Carica papaya, Momordica charantia, Piper betle, Hibiscus rosa, Curcuma domestica, Areca catechu, and Andrographic paniculata. Further research is needed regarding the effects of herbs on human subjects, reversibility effects, and the safety of herbs on health in a long-term use.